'True crime' stories and psychiatrists' ethical responsibilities. (August 2021) - Scott, Russ; Robertson, Michael; Freckelton QC, Ian
Objective: In May 2018, a small paperback book was published, which briefly described 10 cases of persons charged with murder whom an Australian psychiatrist had assessed for the court. This article considers the ethical issues raised by identifying both the persons charged with murder and their victims in newspaper articles and interviews to promote a book. Conclusions: When persons who have committed homicide are named in a 'true crime' book, their recovery trajectory may be prejudiced and the families of their victims may be re-traumatised. Such publications may also contribute to the stigmatisation of persons with mental illness who commit serious offences. Respect for the dignity of the person is fundamental to the ethical practice of forensic report-writing. There can never be any implied agreement or consent that a psychiatrist who writes a report for the court can also use the material in a book written for profit. The Royal Australian and New Zealand College of Psychiatrists Code of Ethics includes several principles relevant to psychiatrists who write medico-legal reports. Psychiatrists should carefully consider the ethical issues raised in publishing outside of textbooks and professional journals and engaging with the lay media.